UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENGGUNAAN ALAT BANTU VIDEO PEMBELAJARAN DI KELAS 6 SDN TIUHBALAK PASAR - Sudarno (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2018)
This study aims to explain that the action of teachers to implementlearning model using learning video aids in grade 6 of Tiuhbalak Market PrimarySchool, Baradatu, Way Kanan, able to improve learning result of Mathematics.The method used is Observation and demonstration for collecting test data,which is held at the end of each cycle.This study was conducted in three cycles, it can improve student learningoutcomes with the following details (1) Category the highest score in the firstcycle reached 70%, the second cycle 85% and 90% third cycle. (2) The lowestscore category in the first cycle is 55%, the second cycle is 40% and in the thirdcycle is 15%. (3) Category of Average Scores in first cycle 60.2%, Second cycle64.4% and third 78%.